Knowledge Management Systems in Higher Education: A Comprehensive Study through Systematic Literature Review and Bibliometric Analysis (2019-2023) - Faldesiani, Riske; Senen, Syamsul Hadi (The Eastasouth Management and Business, 2024)
The objective of this study is to critically examine the existing body of literature on Knowledge Management Systems (KMS) in the context of higher education. The research employed the PRISMA technique (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) together with a bibliometric approach and computational mapping analysis utilizing VOS Viewer. The study period used as literature data material is Scopus-indexed articles and conference papers from 2019 to 2023. The keywords used were "knowledge, management, system, and higher education". From 313 references that were considered relevant, data reduction was carried out with inclusion and exclusion criteria. Analysis was conducted on 10 articles with the highest number of citations and 5 articles that specifically used the keyword "human resource management". The findings of this study offer a comprehensive outline for future research on human resource management in higher education, specifically focusing on knowledge management systems.